Flipping the Script: Measuring Both Performance Validity and Cognitive Ability with the Forced Choice Recognition Trial of the RCFT. Issue 4 (August 2021) - Abeare, Kaitlyn; Romero, Kristoffer; Cutler, Laura; Sirianni, Christina D.; Erdodi, Laszlo A.
In this study we attempted to replicate the classification accuracy of the newly introduced Forced Choice Recognition trial (FCR) of the Rey Complex Figure Test (RCFT) in a clinical sample. We administered the RCFT FCR and the earlier Yes/No Recognition trial from the RCFT to 52 clinically referred patients as part of a comprehensive neuropsychological test battery and incentivized a separate control group of 83 university students to perform well on these measures. We then computed the classification accuracies of both measures against criterion performance validity tests (PVTs) and compared results between the two samples. At previously published validity cutoffs (≤16 & ≤17), the RCFT FCR remained specific (.84–1.00) to psychometrically defined non-credible responding. Simultaneously, the RCFT FCR was more sensitive to examinees' natural variability in visual-perceptual and verbal memory skills than the Yes/No Recognition trial. Even after being reduced to a seven-point scale (18-24) by the validity cutoffs, both RCFT recognition scores continued to provide clinically useful information on visual memory. This is the first study to validate the RCFT FCR as a PVT in a clinical sample. Our data also support its use for measuring cognitive ability. Replication studies with more diverse samples and different criterion measures are still needed before large-scale clinical application of this scale.